2018
DOI: 10.1097/phm.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Mechanical Response of Deep Dorsal Neck Muscles in Individuals Experiencing Whiplash-Associated Disorders Compared to Healthy Controls

Abstract: Advanced ACCREDITATION: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians.The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 0.5 AMA PRA Category 1 Credit(s)™. Physicians should only claim credit commensurate with the extent of their participation in the activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Earlier research regarding deformation rate in prone weighted neck extension showed the highest deformation rate for the multifidus muscle, compared with other dorsal muscles, in individuals with good neck health 18,37 as well as in patients with whiplash-associated disorders tested in a sitting task when stabilizing the neck during arm lifts. 22 The multifidus muscle has also been shown to have the highest deformation rate in patients who have undergone anterior cervical decompression and fusion for cervical disc disease and healthy controls when tested in isometric contractions in neck extension.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier research regarding deformation rate in prone weighted neck extension showed the highest deformation rate for the multifidus muscle, compared with other dorsal muscles, in individuals with good neck health 18,37 as well as in patients with whiplash-associated disorders tested in a sitting task when stabilizing the neck during arm lifts. 22 The multifidus muscle has also been shown to have the highest deformation rate in patients who have undergone anterior cervical decompression and fusion for cervical disc disease and healthy controls when tested in isometric contractions in neck extension.…”
Section: Discussionmentioning
confidence: 97%
“…demonstrated increasing strain values in relation to external force outputs of the BB in five healthy individuals using a former ultrasonography technology that had approximately half the sampling frequency (38-50 Hz) as the current technology (>140 Hz). Rahnama et al [10] recently used custom-made software to process the unique speckle pattern formed by the acoustic ultrasound waves that were scattered and reflected upon hitting the muscles. They reported strain values for healthy dorsal neck muscles (11–34%) that were very similar to those in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Within-session reliability of STU was demonstrated in a study of deep dorsal neck muscles, but this did not clearly define whether the reliability of strain parameters was calculated within or between test sessions [22]. Finally, differences in strain between individuals with whiplash-associated disorders and healthy controls have been shown [10]. However, the study did not provide evidence of an association between strain parameters and varying external loading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations